2017
DOI: 10.1007/s10040-017-1559-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ionic strength and organic matter on virus inactivation at low temperatures: general likelihood uncertainty estimation (GLUE) as an alternative to least-squares parameter optimization for the fitting of virus inactivation models

Abstract: This study examined how the inactivation of bacteriophage MS2 in water was affected by ionic strength (IS) and dissolved organic carbon (DOC) using static batch inactivation experiments at 4°C conducted over a period of 2 months. Experimental conditions were characteristic of an operational managed aquifer recharge (MAR) scheme in Uppsala, Sweden. Experimental data were fit with constant and time-dependent inactivation models using two methods: (1) traditional linear and nonlinear least-squares techniques; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The model input distributions obtained through inverse modelling can be used as input in forward analysis in the other quadrants, as is often done (e.g. Fonseca et al, 2014;Mayotte et al, 2017;Inam et al, 2017). However, this requires some additional assumptions regarding extrapolation and stationarity (figure 7.1).…”
Section: Stationarity Extrapolation and Stationaritymentioning
confidence: 99%
See 1 more Smart Citation
“…The model input distributions obtained through inverse modelling can be used as input in forward analysis in the other quadrants, as is often done (e.g. Fonseca et al, 2014;Mayotte et al, 2017;Inam et al, 2017). However, this requires some additional assumptions regarding extrapolation and stationarity (figure 7.1).…”
Section: Stationarity Extrapolation and Stationaritymentioning
confidence: 99%
“…Formally, this is achieved through Bayesian inference, which produces probability distributions of parameter values given the (subjective) likelihood that the model, given these values, confirms experimental observation. A well known Bayesian inference methodology is GLUE (generalised likelihood uncertainty estimation), originally developed for non-uniqueness problems in hydrology (Beven and Binley, 1992;Fonseca et al, 2014;Mayotte et al, 2017). However, previous work has shown that estimating more than one friction source based on water levels can result in unidentifiable parameter distributions, which are characterised by wide and unconstrained shapes (Werner et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%